The impact of environmental, social, and governance (ESG) factors on firm financial performance and stock prices: evidence from the FTSE Bursa Malaysia Emas index (FBMEMAS) - Chew, Li Eng (2025)
This dissertation examines the impact of ESG ratings on firm financial performance and stock prices among companies listed on the FBMEMAS Index from 2021 to 2023. ESG ratings are sourced from FTSE Russell, while financial performance is measured using ROA and ROE. Stock price performance is assessed based on the closing stock price at the end of each financial year.